95.6k views
4 votes
X²-4x+3=0, then what is the value of (x-2)²=?​

User Learner
by
5.2k points

1 Answer

5 votes

Answer:

We conclude that:


\left(x-2\right)^2=1

Explanation:

Given the expression


x^2-4x+3=0

subtract 3 from both sides


x^2-4x+3-3=0-3


x^2-4x=-3

Add -2² to both sides


x^2-4x+\left(-2\right)^2=-3+\left(-2\right)^2

simplify


x^2-4x+\left(-2\right)^2=1

Applying the perfect square formula: (a-b)² = a²-2ab+b²

so


\left(x-2\right)^2=1
x^2-4x+\left(-2\right)^2=\left(x-2\right)^2

Therefore, we conclude that:


\left(x-2\right)^2=1

User Omar Magdy
by
5.5k points